Nacre-inspired integrated strong and tough reduced graphene oxide–poly(acrylic acid) nanocomposites. Issue 10 (19th February 2016) - Wan, Sijie; Hu, Han; Peng, Jingsong; Li, Yuchen; Fan, Yuzun; Jiang, Lei; Cheng, Qunfeng
Abstract : Inspired by the relationship between interface interactions and the high performance mechanical properties of nacre, a strong and tough nacre-inspired nanocomposite was demonstrated based on graphene oxide (GO) and polyacrylic acid (PAA) prepared via a vacuum-assisted filtration self-assembly process. Abstract : Inspired by the relationship between interface interactions and the high performance mechanical properties of nacre, a strong and tough nacre-inspired nanocomposite was demonstrated based on graphene oxide (GO) and polyacrylic acid (PAA) prepared via a vacuum-assisted filtration self-assembly process. The abundant hydrogen bonding between GO and PAA results in both high strength and toughness of the bioinspired nanocomposites, which are 2 and 3.3 times higher than that of pure reduced GO film, respectively. In addition, the effect of environmental relative humidity on the mechanical properties of bioinspired nanocomposites is also investigated, and is consistent with previous theoretical predictions. Moreover, this nacre-inspired nanocomposite also displays high electrical conductivity of 108.9 S cm −1 . These excellent physical properties allow this type of nacre-inspired nanocomposite to be used in many applications, such as flexible electrodes, aerospace applications, and artificial muscles etc. This nacre-inspired strategy also opens an avenue for constructing integrated high performance graphene-based nanocomposites in the near future.